Configuration Synthesis of a Spherical Coaxial-Actuated Parallel Mechanism for In-Situ Machining Robots - Yang Qi; Yuhuan Wu; Wenrui Yu (IEEE Access)
Large-scale curved structural components often exhibit irregular and continuously varying geometries, requiring precise machining with high smoothness and microstructural integrity. In-situ machining robots offer a flexible and efficient solution, with coaxial-driven mechanisms standing out for their self-centering motion and structural simplicity, effectively reducing the coupling issues common in hybrid systems. This study investigates the topological synthesis of such mechanisms using Finite Instantaneous Screw (FIS) theory. The motion characteristics of the end-effector are first described via finite screws, then embedded into standardized limb structures to construct viable topologies. By applying the properties of the screw triple product, equivalent rotational and translational motions are derived, leading to extended and variant limb configurations. The feasibility is verified through FIS-based configuration synthesis. Three fully symmetrical coaxial-driven parallel mechanisms are designed to meet assembly and application requirements. A systematic topological synthesis method is proposed, providing new models that lay a theoretical foundation for future development of in-situ machining systems.